The degenerate Carathéodory problem and the elementary multiple factor - Chernovol, N. N. (Журнал математичної фізики, аналізу, геометрії, 2005)
The degenerate matricial interpolation Carathéodory problem is solved. To solve this problem we use the V.P. Potapovʼs approach based on the theory of $J$-expansive matrix-functions. The $\mathcal{K}$-type subspace technique also plays an important role in these investigations. Mathematics Subject Classification: 30E05, 47A56, 30D50.